POLITE EXPRESSIONS USED BY TEACHERS IN TEACHING ENGLISH IN THE CLASSROOM - Masykur Rauf (Elite : English and Literature Journal, 2015)
Abstract The objectives of this research were to find out the kinds of polite expressions used  by  teachers  in  teaching  English  in  the  classroom  and  effects  of  polite expressions  used  by  teachers  to  students.  The researcher applied descriptive qualitative research and used purposive sampling in getting the data. The subject of this research was one English teacher of SMP 24 Makassar.  The researcher did classroom observation by recording the teacher’s activities and analyzed it through Brown  and  Levinson’s theory of politeness strategies. The researcher found  that  some  polite  expressions  of  strategies  that  the  teacher  used is divided  into  two  types.  First,  Positive  Politeness  (PP) such as  greetings, notice and attend the  hearer, exaggerate, intensify interest of hearer, use in-group identity makers, seeking agreement,  presuppose/  raise/  assert  common  ground,  include  both  speaker and  hearer  in  the  activity,  giving  or  asking  reasons,  assume  or  assert reciprocity and giving gifts to hearer (goods, sympathy); and Negative Politeness (NP)  such  as  Being conventionally indirect, Questions, Minimize the imposition, Giving deference, Apologize,  Nominalize.  The effects to students are:  being motivated in their study, student’s attitude (affective), respect to teacher, self-confidence, being active and attending in teaching learning process, and honest.Abstrak Ekspresi Kesopanan yang Digunakan oleh Guru dalam Mengajar Bahasa Inggris di Kelas. Tujuan dari penelitian ini adalah untuk mengetahui jenis ekspresi kesopanan yang digunakan oleh guru dalam mengajar bahasa Inggris di kelas dan efek dari ekspresi kesopanan yang digunakan oleh guru kepada siswa. Ini adalah penelitian deskriptif kualitatif yang menggunakan purposive sampling untuk mendapatkan data. Subjek penelitian ini adalah salah seorang guru Bahasa Inggris SMP 24 Makassar. Peneliti melakukan observasi kelas dengan merekam aktivitas guru dan dianalisis meggunakan teori strategi kesantunan Brown dan Levinson. Peneliti menemukan bahwa ekspresi kesopanan yang digunakan guru dibagi menjadi dua jenis. Pertama, Kesopanan Positif (KP) seperti salam, pemberitahuan dan menyapa pendengar, membesar-besarkan, mengintensifkan kepentingan pendengar, gunakan pembuat identitas dalam kelompok, mencari kesepakatan, mengandaikan / angkat / menegaskan, mengikutsertakan pembicara dan pendengar dalam kegiatan, memberi atau meminta alasan, mengasumsikan atau menegaskan timbal balik dan memberikan hadiah kepada pendengar (barang, simpati); dan kesopanan negatif (np) seperti menjadi konvensional tidak langsung, pertanyaan, minimalkan pembebanan, memberikan rasa hormat, minta maaf, nominalize. Efek untuk siswa: termotivasi dalam pelajaran mereka, sikap siswa (afektif), sehubungan dengan guru, kepercayaan diri, aktif dan menghadiri proses belajar mengajar, serta jujur.